2017
DOI: 10.1016/j.neuropharm.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influence of cys407* Grm2 mutation in Hannover-derived Wistar rats: mGlu2 receptor loss links to alcohol intake, risk taking and emotional behaviour

Abstract: Modulation of metabotropic glutamate 2 (mGlu2) receptor function has huge potential for treating psychiatric and neurological diseases. Development of drugs acting on mGlu2 receptors depends on the development and use of translatable animal models of disease. We report here a stop codon mutation at cysteine 407 in Grm2 (cys407*) that is common in some Wistar rats. Therefore, researchers in this field need to be aware of strains with this mutation. Our genotypic survey found widespread prevalence of the mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 97 publications
4
43
0
Order By: Relevance
“…Moreover, the results obtained with DOI and clozapine + MK-801 on PPI are consistent with the finding that the RHA-I strain has an alteration of the 5-HT2A/mGluR2 complex (i.e., a deficit of mGlu2 receptors and a relative increase of 5-HT2A receptors; Klein et al 2014; Wood et al 2016), similar to that observed in schizophrenic patients (Gonzalez-Maeso et al 2008). Thus, RHA-I rats may represent a model of dopamine- and 5-HT2A/mGluR2-related schizophrenia-relevant features.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the results obtained with DOI and clozapine + MK-801 on PPI are consistent with the finding that the RHA-I strain has an alteration of the 5-HT2A/mGluR2 complex (i.e., a deficit of mGlu2 receptors and a relative increase of 5-HT2A receptors; Klein et al 2014; Wood et al 2016), similar to that observed in schizophrenic patients (Gonzalez-Maeso et al 2008). Thus, RHA-I rats may represent a model of dopamine- and 5-HT2A/mGluR2-related schizophrenia-relevant features.…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, the expression of psychotic states by 5-HT receptor agonists and antipsychotic effects by atypical antipsychotic drugs (i.e., 5-HT receptor antagonists) requires the presence of both 5-HT2A and mGluR2 receptors (Fribourg et al 2011; Gonzalez-Maeso et al 2008; Klein et al 2014). Remarkably, as reported by Klein et al (2014), RHA-I rats showed no detectable protein levels of mGlu2 receptor protein in the frontal cortex, hippocampus, and the striatum, a deficit that is apparently due to a mutation in the grm2 gene (Wood et al 2016). Thus, in line with the above evidence, it seems plausible that the reduced PPI-impairing effects of DOI in RHA-I rats (relative to RLA-Is) may be due to their low cerebral density of mGluR2 receptors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Intercrossing studies suggest that this allele is directly linked to increased alcohol consumption and preference in P rats (Zhou et al, 2013). Further investigation of lines of rats selectively bred for alcohol-related behaviors has also revealed an association between Grm2 * 407 and alcohol consumption (Wood et al, 2016). Importantly, this mutation is also present in many commercially available rat lines; therefore, extreme care must be taken when choosing strains and sources of rats for studying drug seeking and taking, particularly in regards to evaluating the effects of mGlu 2 on drug-related behaviors.…”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…Importantly, this mutation is also present in many commercially available rat lines; therefore, extreme care must be taken when choosing strains and sources of rats for studying drug seeking and taking, particularly in regards to evaluating the effects of mGlu 2 on drug-related behaviors. Conversely, rats lacking mGlu 2 can serve as valuable controls for the specificity of mGlu 2 -targeted drug effects (Augier et al, 2016; Wood et al, 2016). …”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%